How the Law Really Works: The New Sociology of Law in Russia - Dzmitryieva, Aryna (Journal of Economic Sociology, 2013)
The paper is devoted to the sociological turn in law studies in Russia. The sociology of law is a new concept for the Russian sociology and is not widely recognized as a discipline with own developed theoretical background and research methods. One of the recent developments that gave rise to the new sociology of law in Russia was the creation in 2009 of the Institute for the Rule of Law (IRL) in the European University at Saint Petersburg. The mission of the Institute is to facilitate judicial and law enforcement reforms and to uphold the principle of the rule of law in Russia. This goal is pursued by means of academic and policy-oriented study conducted within the research tradition known as Law and Society, which is way beyond pure sociology of law and takes advantage of related disciplines, such as economic sociology, new institutional economics, law and economics, political science and others. In the brief overview, the author addresses four most interesting areas of studies. First, it refers to extra-legal influences on court decisions that can result in regularities implicit in the decision making process in arbitration and civic courts in Russia. Second, it provides sociological views on judges as a professional community. Third, it proposes an institutional analysis of the judicial decisions that are overwhelmingly biased towards prosecution. Fourth, it discusses issues of copyright law and its implications, especially under faster development of the Internet technologies. Reviewing the fourth research areas, the author demonstrates how sociologists challenge this autonomy of law and study external social influences. Thus, they shows “law in action” in a real society.